Selection of scented rice (Oryza sativa) and its value-addition for higher profitability - Manjunath, B L; Desai, H.R Prabhu; Talaulikar, Sunetra; Korikanthimath, V S (The Indian Journal of Agricultural Sciences, 2008)
Field experiments were conducted during 2004-06 at ICAR Research Complex for Goa, to assess the feasibility of improving profitability from rice cultivation through introduction of suitable scented rice varieties and their value-addition. The trials involved comparison of 7 scented rice varieties, viz. ’Kasturi’, ’Pusa Sugandh 2’, ’Pusa Sugandh 3’, ’Pusa Sugandh 5’, ’Vasumati’, ’Mugad Sugandh’ and ’Pusa Basamti 1’ in randomized block design with 3 replications. The pooled mean grain yield of ’Pusa Sugandh 5’ was significantly superior (4.66 tonnes/ha) over ’Pusa Basmati 1’. The milling per cent of the varieties ranged from 60 to 68% with ’Pusa Sugandh 5’ recording 67% milling. Highest gross and net retums (Rs 61 705/ha, and Rs 29 885/ha respectively) were obtained especially with variety ’Pusa Sugandh 5’ indicating the feasibility of enhancing the net retums by 72%.through processing and value addition.